1997
DOI: 10.1159/000201420
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Stimulates Production of Glycoconjugate Layers on the Cell Surface of Gastric Surface Mucous Cell Line GSM06

Abstract: The mechanism of regulation of mucus production in the gastric mucosa remains unclear. Recently, we established a gastric surface mucous cell line GSM06, which produces periodic acid-Shiff (PAS)-positive glycoconjugate (mucus) layers on the cell surface, from transgenic mice harboring a temperature-sensitive simian virus 40 large T-antigen gene. In this study, GSM06 cells were examined for its production of PAS-positive glycoconjugate layers to acid secretagogues and growth factors. The cells were cultured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…3 B). However, when cells were kept confluent over 3 d, PAS-positive materials appeared as described previously (25,26). In contrast, when the cells were transferred from 33 to 39ЊC for 48 h, the cells became clearly positive for PAS staining in low or high cell density (Fig.…”
Section: Characteristics Of Gastric Mucosal Cells Of Fetal and Adult supporting
confidence: 68%
See 1 more Smart Citation
“…3 B). However, when cells were kept confluent over 3 d, PAS-positive materials appeared as described previously (25,26). In contrast, when the cells were transferred from 33 to 39ЊC for 48 h, the cells became clearly positive for PAS staining in low or high cell density (Fig.…”
Section: Characteristics Of Gastric Mucosal Cells Of Fetal and Adult supporting
confidence: 68%
“…Morphologically, GSM06 cells are rounded or polyhedral as is typical of primary cultured gastric surface mucous cells (10,(19)(20)(21). Electron microscopy revealed that the cells contained a small number of secretory granules (26). The PAS-positive staining of the GSM06 cells appeared to be due to glycoproteins and glycolipids, but not to mucin molecules (27).…”
Section: Introductionmentioning
confidence: 94%
“…The cells were cultured with DMEM supplemented with 0.5% FBS for 24 h at 33°C, followed by incubation in DMEM supplemented with 0.5% FBS and BPA for 24 h at 33°C. The cell viability was determined using a tetrazolium compound, 4-[3-(4-idophenyl)-2-(4-nitrophenyl)-2H-5-tetra-zolio]-1,3-benzene disulfonate (1a) sodium salt (WST-1), according to our previous report (8).…”
mentioning
confidence: 99%
“…These reports suggest that these agents induce not only acid secretion but also strengthen the gastric mucosal barrier. In contrast, Tabuchi et al 13 reported that these agents did not increase glycoconjugate production in mucous cell lines. Analysis of carbohydrates in gastric aspirates in normal subjects in response to pentagastrin, an acid-stimulating agent, revealed little difference in the sialic acid concentration either in the purified mucin or non-fractionated gastric aspirations.…”
Section: Introductionmentioning
confidence: 89%